Sleep, Affect, and Social Competence from Preschool to Preadolescence: Distinct Pathways to Emotional and Social Adjustment for Boys and for Girls - Foley, Joan E.; Weinraub, Marsha (Frontiers in Psychology, 2017)
Using a normative sample of 1,057 children studied across 4 waves over 6 years with multiple informants, we investigated transactional relations for sleep problems, anxious-depressed symptoms, and social functioning from preschool to preadolescence, assessing cumulative effects on children’s emotional and social adjustment. To examine sex differences in the developmental processes, we conducted separate analyses for boys and girls. For both boys and girls, longitudinal cross-lagged panel analyses showed that preschool sleep problems directly predicted anxious-depressed symptoms 2 years later; indirect effects continued into preadolescence. For girls, early and later sleep problems directly or indirectly predicted a wide variety of preadolescent emotional and social adjustment domains (e.g., depressive symptoms, school competence, emotion regulation, risk-taking behaviors). For boys, social competence played a more important role than sleep problems in predicting preadolescent adjustment. Among the first set of findings that demonstrate longitudinal relations between sleep problems and social functioning in middle childhood and preadolescence, these results support Dahl’s and Walker’s neurological models of sleep and emotional functioning. We discuss these findings in light of relations between sleep and affect during pre-pubertal developmental and discuss differential findings for boys and girls.